PROBLEMS IN THEORY OF EPIDEMIOLOGY AND POSSIBLE ROUTES OF ITS DEVELOPMENT (TO THE DISCUSSION ON THE ARTICLE BY SERGEY L. KOLPAKOV) - ALEXANDR B. Belov (Фундаментальная и клиническая медицина)
Here I critically review conventional concepts in the national theory of epidemiology to denote promising routes in its development for improving terminology, systematics, and teaching of this discipline in medical universities. I propose that the progress in epidemiological theory should be based on Belyakov model of epidemic process in anthroponoses and must be accompanied by current data from the modern fields of biomedicine. The united ecological approach to form laws of disease spreading may eventually lead to the integration of biomedical disciplines.